Contribution of Defective PS Recognition and Efferocytosis to Chronic Inflammation and Autoimmunity - Kimani, Stanley Gititu; Geng, Ke; Kasikara, Canan; Kumar, Sushil; Sriram, Ganapathy; Wu, Yi; Birge, Raymond B. (Frontiers in Immunology, 2014)
Rapid and efficient clearance of apoptotic cells results in elimination of auto-antigens and provides a strong anti-inflammatory and immunosuppressive signal to prevent autoimmunity. While professional and non-professional phagocytes utilize a wide array of surface receptors to recognize apoptotic cells, recognition of phosphatidylserine (PS) on apoptotic cells by PS receptors on phagocytes is emblematic signal for efferocytosis in metazoans. PS-dependent efferocytosis is associated with production of anti-inflammatory factors such as IL-10 and TGF-β that function, in part, to maintain tolerance to auto-antigens. In contrast, when apoptotic cells fail to be recognized and processed for degradation, auto-antigens persist, which can trigger immune activation leading to autoantibody production and autoimmunity. Despite the fact that genetic mouse models clearly demonstrate that loss of PS receptors can lead to age-dependent autoimmune diseases reminiscent of systemic lupus erythematosus (SLE), link between PS and defective clearance in chronic inflammation and human autoimmunity is not well delineated. In this hypothesis and theory, we review emerging questions developing in the field that may be of relevance to SLE and human autoimmunity.